PENGARUH CONTENT MARKETING TIKTOK AFFILIATE TERHADAP MINAT BELI PADA MAHASISWA EKONOMI SYARIAH TAHUN 2020 IAIN METRO - Soleha, Selly Lathifa (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2025)
The rapid development of technology is currently starting to influence aspects of life, especially in the world of marketing. Marketing is currently starting to use digital media, one of which is content marketing. Content marketing can provide an attraction that can encourage consumers' buying interest to buy the products being marketed. Content marketing is currently widely used in social media applications, namely TikTok. The presence of TikTok with the TikTok affiliate feature can make it easier for companies to market their products. This feature is quite easy, just use content or videos that can attract consumers' attention, then in the content a link is included that can directly connect to the product being marketed. This research aims to determine and analyze the influence of TikTok affiliate content marketing on purchasing interest among Islamic economics students in 2020 IAIN Metro. This research uses a quantitative method which is a calculation based on statistical data in the form of amounts or figures. The technique used in sampling in this research was a probability sampling techque using proportional random sampling. Meanwhile, the sample in this research was 65 students. The data analysis tools in this research are validity test, reliability test, classical assumption test, simple linear regression test, t test and coefficient of determination test. The results of this research show that TikTok affiliate content marketing has a significant effect on the buying interest of Islamic economics students in 2020 IAIN Metro. This is because the value of sig.0.00 < 0.05 or the value of t_count > t_table (9.415 > 1.669). Then through the R square test it was 0.585 (58.5%) while the remaining 41.5% was influenced by other things outside the scope of this research